Culture and Enaction. An approach from a Lexical Study of the Spanish Online Press. - Luque-Nadal, Lucía (Université Clermont Auvergne, 2024)
In this paper we will pay attention to the convergence of enaction and culture in human lexicon. To that end, we will carry out an analysis of real interactions of a special type of computer-mediated communication (CMC), i.e., the comment’s sections of several Spanish digital newspapers. Our aim is to explain how both an enactive and cultural analysis of our corpus, based on authentic readers’ comments, lead to a more comprehensive explanation of the cognitive and thematically related networks from a discursive point of view.
Keywords: Interacción hombre-ordenador; Periódicos electrónicos - España - Lenguaje; Lexicología; Sociolingüística; Enaction; Culture; Lexicon; Cognition; Computer-mediated communication (CMC)